Winnie-the-Pooh [compact disc, unabridged] - Milne, A. A. (Alan Alexander), 1882-1956 (Listening Library, 2009)
Random House presents a collection of classic Winnie-the-Pooh stories packed with everyone's favorite characters: Pooh, Piglet, Eeyore, Tigger, Kanga, and Christopher Robin.